THE PARTICULARITIES OF THE INITIAL PUBLIC OFFERING PROCESS IN THE UNITED STATES OF AMERICA - Vladimirović, Ivana (Ekonomija - teorija i praksa, 2022)
Initial public offering (IPO) presents a special mode of emission when a company for the first time publicly emits shares that are available to a wide scope of investors, institutions and individuals. IPO is a huge step that companies are willing to take only after a detailed analysis of their current situation, as well as advantages, disadvantages and potential risks that this action entails. The greater part of initial public offering is done through investment banks as specialized and highly professional financial institutions, which help the issuers when estimating opportunities for placing securities on the primary capital market and also offering various other services. The aim of this paper is to present the particularities of the IPO process in accordance with the legal regulations of the United States of America. Since determining the adequate price of the shares of IPO is the most sensitive part, that most often the success of the whole process depends on, a concise analysis of the key methods and factors influencing price formation is presented at the end of the paper.